Anti-proliferative and Apoptotic Activities of Kasturi Tobacco (Nicotiana tabacum L.) Leaf Resinoid on Cervical Cancer Cell - Banun Kusumawardani; Larissa Tania; Ari Satia Nugraha (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Cervical cancer has a high rate of morbidity and mortality in women with cancer. Recent studies have found that tobacco (Nicotiana tabacum L.) is a potential source of anti-cancer agents. Hence, this study was conducted to determine the potential of Kasturi tobacco leaf resinoids as apoptotic agents against cervical cell malignancies, since it has not been fully elucidated before.METHODS: The phytochemical diversity of Kasturi tobacco resinoids was generated by gas chromatography-mass spectrometry (GC-MS) analysis followed by spectral similarity to National Institute of Standards and Technology (NIST) database. Cytotoxicity and proliferative activity of HeLa cells treated with Kasturi tobacco resinoids at various concentrations were evaluated by MTT assay. The expression of Caspase-3, cyclooxygenase-2 (COX-2) and heat shock protein 90 (HSP-90) in HeLa cells was analyzed by immunocytochemistry. Next, the migration ability of HeLa cells was observed by the scratch method.RESULTS: Kasturi tobacco resin contains 4,8,13-cyclotetradecatriene-1,3-diol, 1,5,9-trim with α-2,7,11-cembratriene-4,6-diol (α-CBD) structure in the form of a diterpenoid compound with the chemical formula C20H34O2 and a molecular weight of 306 Da. Kasturi tobacco resinoid with IC50 value of 2500 μg/mL inhibited proliferative activity during 72 hours. At a concentration of 1¼ IC50 and incubation for 48 hours, Caspase-3 expression increased by 74.1%, while COX-2 and HSP-90 expression decreased by 28.3% and 26.1%, respectively. HeLa cell migration was inhibited by Kasturi tobacco resinoid at 24 hours incubation.CONCLUSION: Kasturi tobacco resinoids with a concentration of 1¼ IC50 have potential as cervical anti-cancer agents by increasing Caspase-3 expression and decreasing COX-2 and HSP-90 expression within 48 hours.KEYWORDS: Kasturi tobacco resinoids, cervical cancer, anti-cancer agent, proliferative activity